Just Price Incentives to Decrease Personal Carbon Footprints - Oskari Sivula (Editura Academiei Romane, 2022)
This article examines taxation as a way to guide individuals to decrease their carbon footprints and what justice requires from us when designing such taxes. This article suggests that from the perspective of local distributive justice if taxes are used to guide people to behavioural changes the taxes should be sensitive to people’s ability to pay. This is because flat taxes tend to hit the less well-off harder than the prosperous. Furthermore, according to the “ability to pay” principle when people are bound to contribute to a common project we should not make those who are already worst-off more worse off. Following this, three further arguments are considered for why taxes aimed to diminish personal emissions should be sensitive to people’s ability to pay. First, in the case of flat carbon taxes, the burdens are not distributed equally because the relevant burden in question is not the price paid but the act or effort of changing behaviour. Second, a carbon tax that directs all to emission reductions is more effective in achieving these reductions precisely because it directs all and not just certain income groups to mitigate personal emissions. Finally, it is argued that reflecting external costs and discouraging consumption are different things. Further on, because of the nature of climate change, a carbon tax should be designed to discourage consumption and not merely to reflect external costs. A carbon tax that is sensitive to different abilities to pay is better in achieving this than a flat carbon tax.